Improving Reading and Writing Achievements through Whole Language Approach - Binti Koniaturrohmah (Jurnal Bahasa dan Sastra, 2018)
Abstract: The main purpose of this study was to find out whether or not whole language ap- proach could make a difference in improving both students’ reading and writing achievements. The research was conducted in terms of reading and writing intervention for about two months or 24 meetings including pre and post-tests. The tests were reading comprehension and writ- ing. The findings showed that (1) there was a significant progress within each group in both reading and writing. (2) there was also significant mean difference between the experimental and control groups with the contribution of the Whole Language Approach to students’ reading comprehension by 99.2% and to writing achievements by 87.2%.Keywords: whole language approach, reading achievement and writing achievement.Abstrak: Tujuan utama dari penelitian ini adalah untuk mengetahui apakah pendekatan whole language dapat membuat suatu perbedaan dalam meningkatkan prestasi siswa dalam membaca dan menulis. Penelitian ini dilakukan dalam hal intervensi membaca dan menulis selama se- kitar dua bulan atau 24 pertemuan termasuk tes awal dan tes akhir. Tesnya adalah pemahaman membaca dan menulis. Hasilnya menunjukkan bahwa (1) ada kemajuan yang signifikan dalam masing-masing kelompok dalam membaca dan menulis. (2) ada juga perbedaan rata-rata yang signifikan antara kelompok eksperimen dan kontrol dengan kontribusi dari Pendekatan Whole Language untuk prestasi siswa dalam pemahaman membaca sebesar 99,2% dan menulis sebe- sar 87,2%.Kata-kata kunci: pendekatan whole language, prestasi membaca dan menulis